Leading Edge Modification of NACA 0015 and NACA 4415 Inspired by Beluga Whale - James Julian; Waridho Iskandar; Fitri Wahyuni (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2023)
This research modifies the leading-edge structure of NACA 0015 and NACA 4415 to resemble the nose of a beluga whale. The focus of this modification is to improve the airfoil's aerodynamic performance and investigate the changing fluid flow patterns. Numerical equation used is RANS combined with the k-epsilon turbulence model. Mesh independence test shows that mesh with 200 elements is the best mesh. Validation results reveal that CFD data can follow the trend of experimental data, especially on the AoA before the stall. There was a significant increase in Cl from NACA 0015 and NACA 4415 at AoA>9°. On the other hand, the modification also had a positive effect by lowering the Cd value. The modification also provides an advantage by increasing the maximum Cl/Cd value. Furthermore, the separation point data shows that the modification can delay the separation of the fluid flow in the airfoil. Modifications can cause an increase in pressure on the lower side and a decrease in pressure on the upper side. Through velocity contours and streamlines, the modifications can reduce the recirculation area. Overall, modifying the leading edge has positive impacts on the NACA 0015 and NACA 4415 airfoils.